Immunosenescence and its related comorbidities in older people living with HIV - Xiao-Yan He; Xiu-Wen Wang; Shuang Li; Na Li; Wei Li; Yan Hu; Na Guo; Yong-Tang Zheng; Hong-Yi Zheng; Bin Su; Haijuan Wang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. With the aging of the global population, older people living with HIV (OPLWH) have emerged as a focal point in HIV/AIDS research. Although antiretroviral therapy has demonstrated positive effects in OPLWH, concerns persist regarding overall poor immune reconstitution and elevated rates of age-related comorbidities, such as cardiovascular disease, bone disease, and cognitive impairment. This review aims to elucidate the mechanisms underlying immunosenescence and the interaction of immunosenescence with HIV infection, further exploring its role in the pathogenesis of HIV infection during aging. Aging-induced involution of the immune system, along with chronic inflammation and infection, can induce immunosenescence, leading to immune dysfunction that impairs the effective control of HIV infection. In addition, HIV infection induces immunosenescence through persistent inflammation and immune activation, even under treatment. The combined effects of aging and HIV infection accelerate the progression of immunosenescence in OPLWH, increasing their susceptibility to multiple age-related diseases. The unfavorable prognosis observed among OPLWH is largely attributed to increased levels of immunosenescence. A comprehensive understanding of the relationship between immunosenescence and HIV infection is crucial for developing targeted therapeutic strategies for this vulnerable population.